Regional assessment of contaminant bioaccumulation in sport fish tissue in the Southern California Bight, USA. (November 2021) - McLaughlin, Karen; Davis, Jay; Bonnema, Autumn; Du, Bowen; Ichikawa, Gary; Jakl, William; Heim, Wesley; Schiff, Kenneth
Abstract: Marine recreational fisheries in California are economically and culturally important; however, consumption of contaminated seafood may be a human health risk. The California Environmental Protection Agency Office of Environmental Health Hazard Assessment developed Advisory Tissue Levels (ATLs) to be used in developing consumption recommendations protecting the health of fish consumers. This study characterizes extent and magnitude of bioaccumulation of contaminants in sport fish in Southern California relative to ATLs. Most zones exceeded the ATL for mercury corresponding to consumption of not more than 3 servings per week in one or more target species. A third of zones exceeded the ATL for total polychlorinated biphenyls (PCBs) corresponding to consumption of not more than 7 servings per week. However, neither mercury nor total PCBs exceeded the most restrictive, "do not consume", thresholds in measured tissues. Contaminant concentrations in fish tissues have remained the same or decreased since a similar survey in 2009. Graphical abstract: Unlabelled Image Highlights: Contaminant concentrations in Southern California Bight fish were below CA thresholds advising no human consumption Fish tissue mercury contamination was widespread, with all zones exceeding thresholds corresponding to limited consumption A third of fishing zones exceeded advisory thresholds limiting consumption for total polychlorinated biphenyls (PCBs) Concentrations of contaminants in fish tissues were generally lower in 2018 compared to a similar survey in 2009